An evaluation of three methods of in-hospital cardiac arrest educational debriefing: The cardiopulmonary resuscitation debriefing study. (August 2016) - Couper, Keith; Kimani, Peter K.; Davies, Robin P.; Baker, Annalie; Davies, Michelle; Husselbee, Natalie; Melody, Teresa; Griffiths, Frances; Perkins, Gavin D.
Abstract: Background: The use of cardiac arrest educational debriefing has been associated with improvements in cardiopulmonary resuscitation (CPR) quality and patient outcome. The practical challenges associated with delivering some debriefing approaches may not be generalisable to the UK health setting. The aim of this study was to evaluate the deliverability and effectiveness of three cardiac arrest debriefing approaches that were tailored to UK working practice. Methods: We undertook a before/after study at three hospital sites. During the post-intervention period of the study, three cardiac arrest educational debriefing models were implemented at study hospitals (one model per hospital). To evaluate the effectiveness of the interventions, CPR quality and patient outcome data were collected from consecutive adult cardiac arrest events attended by the hospital cardiac arrest team. The primary outcome was chest compression depth. Results: Between November 2011 and July 2014, 1198 cardiac arrest events were eligible for study inclusion (782 pre-intervention; 416 post-intervention). The quality of CPR was high at baseline. During the post-intervention period, cardiac arrest debriefing interventions were delivered to 191 clinicians on 344 occasions. Debriefing interventions were deliverable in practice, but were not associated with a clinically important improvement in CPR quality. The interventions had no effect on patient outcome. Conclusion: The delivery of these cardiac arrest educational debriefing strategies was feasible, but did not have a large effect on CPR quality. This may be attributable to the high-quality of CPR being delivered in study hospitals at baseline. Trial registration: ISRCTN39758339.